Microbiological Water Quality Close To The Stormwater Outfalls In Recreational Beaches Of Kuwait Bay (Journal of Pharmaceutical Negative Results, 2023)
Kuwait Bay's southern shore is home to several facilities used for various purposes, impacting the beaches' ecosystems and coastal environment. Furthermore, the presence of numerous stormwater outfalls on Kuwait Bay's southern shores may be one of the sources of pollutants that are discharged from these outfalls. This research aims to evaluate the microbiological quality of seawater near 5 selected stormwater outfalls located on Kuwait Bay's recreational water by measuring the levels of microbial bacteria such as fecal coliform (FC), and Escherichia Coli. (E. Coli), and fecal streptococci (FS), and water quality parameters including temperature, pH, electrical conductivity (EC), and dissolved oxygen (DO). The analytical results were compared with Kuwait Environmental Public Authority (EPA) requirements for water discharge to Kuwait Bay to assess the suitability of the beaches for recreational activities. The field results revealed the presence of mildly alkaline seawater samples, a range of fresh to saline water types, and various DO levels from very low to acceptable levels. noteworthy, the microbial indicators were extremely high and far beyond EPA guidelines, demonstrating extensive microbiological pollution at these locations. The mean FC/FS ratios of C18 had the greatest mean FC/FS ratio (16.75), signifying human contamination. C3 and C5 indicated human waste in mixed pollution with averages of (3.45 and 2.34 respectively), whereas C8 and C10 showed human contamination with average values (of 5.98, and 4.21 respectively). It is suggested that the seawater quality close to wastewater outfalls be frequently evaluated and treated using efficient onsite treatment technologies to decrease the amount of polluted wastewater discharged directly to the beaches.